Deficiência hídrica em cultivares de amendoim (Arachis hypogaea L.) - Silva, Almir Dias Alves da (1986)
A greenhouse experiment was carried out in Fortaleza, Ceara, Brasil, in 1985 to assess the effects of water stress on peanut plants. This stress was applied in the early vegetative stage (15 to 55 days after planting) and grain filling stage of growth (55 to 95 days after planting), on the performance of three peanut cultivars, belonging to the Virginia, Spanish and Valencia groups. [...]